Complete mitochondrial genome and phylogenetic analysis of Mystacoleucus lepturus (Teleostei, Cypriniformes, Cyprinidae). Issue 6 (3rd June 2022) - Chen, Xiao Jiang; Song, Lin
Abstract: In this study, we aimed to sequence and annotate the complete mtDNA genome sequence of Mystacoleucus lepturus, which were collected from Luosuojiang River in Menglun area, Yunnan Province, China. The mitochondrial genome was 16, 592 bp in length, comprising 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and two non-coding regions (origin of L-strand replication and control region). The whole genome contained C (26.5%), A (32.5%), T (25.3%), and G (15.7%), with an obvious A + T bias (57.8%). Based on the concatenated amino acids sequences of 13 PCGs of M. lepturus and other 22 fishes, a phylogenetic tree was reconstructed using the maximum-likelihood method. The result of phylogenetic analysis supported a close relationship between M. lepturus and M. marginatus . The fundamental genetic data of M. lepturus would be useful for conservation and phylogeny.